In Interview: Key Features of Contemporary British Drama. (February 2023) - Sierz, Aleks; Günenç, Mesut
Abstract : In this interview on 22 March 2022 in London, Mesut Gunenc talks to theatre critic and historian Aleks Sierz about how his work has influenced contemporary British drama, why he chose the name 'in-yer-face theatre' for 1990s avant-garde plays, and why some writers have rejected the label. They also discuss the differences between experiential and experimental theatre, especially focusing on the work of Anthony Neilson, and finish by considering the key themes that characterize 1990s new writing in Britain. Aleks Sierz is author of the seminal In-Yer-Face Theatre: British Drama Today (Faber, 2001), as well as of other work about new writing and post-war British theatre history. His more recent books include Rewriting the Nation: British Theatre Today (Methuen Drama, 2011), Modern British Playwriting: The 1990s (Methuen Drama, 2012), and Good Nights Out: A History of Popular British Theatre Since the Second World War (Methuen Drama, 2021). He has co-authored, with Lia Ghilardi, The Time Traveller's Guide to British Theatre: The First Four Hundred Years (Oberon, 2015). Mesut Gunenc is Assistant Professor in the Department of English Language and Literature at Adnan Menderes University in Turkey. He is the author of Postdramatic Theatrical Signs in Contemporary British Playwrights (Lambert, 2017) and co-editor, with Enes Kavak, of New Readings in British Drama: From the Post-War Period to the Contemporary Era (Peter Lang, 2021). He is currently a visiting postdoctoral scholar at Loughborough University in the UK.